Comparative Analysis of the Global Transcriptomic Response to Oxidative Stress of Bacillus anthracis htrA-Disrupted and Parental Wild Type Strains - Galia Zaide; Uri Elia; Inbar Cohen-Gihon; Ma’ayan Israeli; Shahar Rotem; Ofir Israeli; Sharon Ehrlich; Hila Cohen; Shirley Lazar; Adi Beth-Din; Avigdor Shafferman; Anat Zvi; et al. (Microorganisms, 2020)
We previously demonstrated that the HtrA (High Temperature Requirement A) protease/chaperone active in the quality control of protein synthesis, represents an important virulence determinant of Bacillus anthracis. Virulence attenuation of htrA-disrupted Bacillus anthracis strains was attributed to susceptibility of ΔhtrA strains to stress insults, as evidenced by affected growth under various stress conditions. Here, we report a comparative RNA-seq transcriptomic study generating a database of differentially expressed genes in the B. anthracis htrA-disrupted and wild type parental strains under oxidative stress. The study demonstrates that, apart from protease and chaperone activities, HtrA exerts a regulatory role influencing expression of more than 1000 genes under stress. Functional analysis of groups or individual genes exhibiting strain-specific modulation, evidenced (i) massive downregulation in the ΔhtrA and upregulation in the WT strains of various transcriptional regulators, (ii) downregulation of translation processes in the WT strain, and (iii) downregulation of metal ion binding functions and upregulation of sporulation-associated functions in the ΔhtrA strain. These modulated functions are extensively discussed. Fifteen genes uniquely upregulated in the wild type strain were further interrogated for their modulation in response to other stress regimens. Overexpression of one of these genes, encoding for MazG (a nucleoside triphosphate pyrophosphohydrolase involved in various stress responses in other bacteria), in the ΔhtrA strain resulted in partial alleviation of the H2O2-sensitive phenotype.